Biological Resistance and Application Properties of Particleboards Containing Nano-Zinc Oxide - Ladislav Reinprecht; Ján Iždinský; Zuzana Vidholdová (Advances in Materials Science and Engineering)
Special particleboards (PBs) proposed for kitchens, bathrooms, hospitals, and some other specific products for interiors should have a sufficient resistance against bacteria, molds, and decaying fungi. This work deals about effects of zinc oxide nanoparticles (nano-ZnO) added into melamine-urea-formaldehyde (MUF) glue in the amounts of 0, 2, 6, 12, or 24% wt. on selected biological, moisture, and strength properties of laboratory-produced one-layer PBs. The nano-ZnO-treated PBs had a higher biological resistance: (1) against the Gram-positive bacterium Staphylococcus aureus by up to ca. 70% and the Gram-negative bacterium Escherichia coli by up to 50%, since their bacterial activities at using 1.0 McFarland bacterial inoculum decreased from 0.38–0.40 by up to 0.12–0.19  ×  108 CFU/ml; (2) against the molds Penicillium brevicompactum and Aspergillus niger by up to ca. 50–63%, since their growth intensities (0–4) on the top surfaces of treated PBs decreased according to a modified EN 15457 from 2.33–2.67 by up to 1.17–1.0; (3) against the brown-rot fungus Coniophora puteana by up to 85.7%, since their weight losses reduced according to a modified ENV 12038 from 17.4% by up to 2.5%. The presence of nano-ZnO in PBs uninfluenced their swelling, water absorption, and bending strength; however, it decreased their internal bond strength by up to 38.8%.